Insight into the role of halogen bond in the activity of d-mandelate dehydrogenase toward halogenated substrates. Issue 18 (4th May 2016) - Guo, Fei; Ye, Lidan; Li, Aipeng; Yang, Xiaohong; Yang, Chengcheng; Yu, Hongwei
Graphical abstract: Highlights: Enzymatic activity toward halogenated compounds may be impeded by the substitution. Halogen bond is specific in the complex of proteins and halogenated compounds. Halogen bond introduction is an efficient strategy in protein engineering. Abstract: Chlorine substitution in mandelate turned its derivatives into less active substrates ford -mandelate dehydrogenase (DMdh). To improve the catalysis of chloro-mandelate, a halogen bond was introduced into the protein–substrate complex by site mutation. The catalytic activity of the resulting mutant A89H toward o -chloromandelate was improved by 5 times. The effect of halogen bond was also observed in the dehydrogenation of m -chloromandelate and p -chloromandelate. Based on these results, a new insight was proposed for the role of halogen bond in enzyme activity, and the introduction of halogen bond was shown as an efficient strategy to optimize the catalytic activity toward halogenated substrates.